Evaluation of performance for IBARAKI biological crystal diffractometer iBIX with new detectors. (13th October 2013) - Kusaka, Katsuhiro; Hosoya, Takaaki; Yamada, Taro; Tomoyori, Katsuaki; Ohhara, Takashi; Katagiri, Masaki; Kurihara, Kazuo; Tanaka, Ichiro; Niimura, Nobuo
<x xml:space="preserve">Abstract</x> The IBARAKI biological crystal diffractometer, iBIX, is a high‐performance time‐of‐flight neutron single‐crystal diffractometer for elucidating mainly the hydrogen, protonation and hydration structures of biological macromolecules in various life processes. Since the end of 2008, iBIX has been available to users' experiments supported by Ibaraki University. Since August 2012, an upgrade of the 14 existing detectors has begun and 16 new detectors have been installed for iBIX. The total measurement efficiency of the present diffractometer has been improved by one order of magnitude from the previous one with the increasing of accelerator power. In December 2012, commissioning of the new detectors was successful, and collection of the diffraction dataset of ribonucrease A as a standard protein was attempted in order to estimate the performance of the upgraded iBIX in comparison with previous results. The resolution of diffraction data, equivalence among intensities of symmetry‐related reflections and reliability of the refined structure have been improved dramatically. iBIX is expected to be one of the highest‐performance neutron single‐crystal diffractometers for biological macromolecules in the world.